Analysis of Success Factors: Self-Management System Using The AHP Method At The Ji’rona Building Project ‘Aisyiyah Hospital Bojonegoro - Rohmat Satriawan, Earlangga; Putra, Nyoman Dita Pahang; Velantika, Griselda Junianda (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2025)
Construction projects require an effective and efficient project management system to achieve the expected development goals. One of the developments in project management is the production of a self-managed project management system, which is a management system that the project owner manages by prioritizing the use of their resources. This study aims to determine the priority scale of the factors and criteria for success in self-management in the Ji’rona Building Construction Project of RSAB. The data collection technique used a quantitative descriptive questionnaire survey in this study. The study involved 24 respondents, including project owners, planning teams, implementation teams, supervisory teams/CM, and self-management expert respondents. The data analysis method uses the AHP (Analytical Hierarchy Process) method to make it easier to make decisions based on several alternative self-management success factors. Based on the results of data analysis, the research identified the results of ranking criteria and sub-criteria in the form of a diagram, as well as changes in the hierarchical structure of the research on the success factors of self-management success. The study concluded that the priority factors for the success of self-management in the Ji’rona RSAB Building Construction Project were quality 0.124, communication 0.120, risk management 0.116, stakeholder satisfaction 0.111, cost 0.110, administration 0.108, resources 0.107, time 0.101, and characteristics of the place 0.089.